A Patient with Fibroepithelial Polyp of the Ureter—A Rare Condition Mimicking Malignancy: A Case Report - Wolfgang Brummeisl; Hans-Martin Fritsche; Elisabeth Huber; Wolf F. Wieland; Roman Ganzer (Case Reports in Urology)
A 61-year-old man presented with hematuria and intermittent right pelvic pain. Intravenous urography showed a tubular filling defect and ureteroscopy a tumor in the right mid ureter. Urine cytology and tumor biopsy showed nonmalignant results. Open surgery was performed, and an intraoperative frozen section revealed a fibroepithelial polyp of the right mid ureter. A fibroepithelial polyp is a rare benign lesion that can occur in childhood but is an important differential diagnosis of an upper urinary tract urothelial cell carcinoma in adults.